Polyethyleneimine (PEI) Mediated siRNA Gene Silencing in the Schistosoma mansoni Snail Host, Biomphalaria glabrata - Knight, Matty (Public Library of Science, 2011)

(untitled)
An in vivo, non-invasive technique for gene silencing by RNA interference (RNAi) in the snail, Biomphalaria glabrata, has been developed using cationic polymer polyethyleneimine (PEI) mediated delivery of long double-stranded (ds) and small interfering (si) RNA. Cellular delivery was evaluated and optimized by using a ‘mock’ fluorescent siRNA. Subsequently, we used the method to suppress expression of Cathepsin B (CathB) with either the corresponding siRNA or dsRNA of this transcript. In addition, the knockdown of peroxiredoxin (Prx) at both RNA and protein levels was achieved with the PEI-mediated soaking method. B. glabrata is an important snail host for the transmission of the parasitic digenean platyhelminth, Schistosoma mansoni that causes schistosomiasis in the neotropics. Progress is being made to realize the genome sequence of the snail and to uncover gene expression profiles and cellular pathways that enable the snail to either prevent or sustain an infection. Using PEI complexes, a convenient soaking method has been developed, enabling functional gene knockdown studies with either dsRNA or siRNA. The protocol developed offers a first whole organism method for host-parasite gene function studies needed to identify key mechanisms required for parasite development in the snail host, which ultimately are needed as points for disrupting this parasite mediated disease.